Vulnerability and adaptation to climate change and variability in semi-arid rural southeastern Arizona, USA - Coles, Ashley R.; Scott, Christopher A. (Natural resources forum, 2009)
Agricultural and livestock producers experiencing climate change and variability are simultaneously subject to other sources of environmental vulnerability, as well as political, social, and economic uncertainty. Producers' adaptive decision making takes into account short‐term seasonal factors, while seeking to preserve livelihood stability over the long term. This study identifies multiple sources of vulnerability for farmers and ranchers in southeastern Arizona, and the adaptive strategies they have adopted including the use of information such as seasonal climate forecasts (SCFs). Interviews with producers and extension agents in Pima and Cochise Counties reveal that the principal climatic risks are drought, floods and frosts, and that groundwater use remains a crucial strategy despite increasing pumping costs. Low risk tolerance and uncertainty of seasonal production and marketing conditions diminish the utility of SCFs as a decision‐making tool. Instead, farmers and ranchers continue to rely on past experience and short‐range forecasts, hedging each year instead of taking significant risks. By examining the role of climate information in complex production decisions, the study shows that access to information is not the principal limitation to improving decision making. Comparison to other regions reaffirms common vulnerabilities among producers and highlights research and communication needs that have global relevance.